Skin structure of small pareiasaurs. With comments on their taxonomy in the Cistecephalus Zone - Findlay, G. H. (Bernard Price Institute for Palaeontological Research, 1970)
The Cistecephalus zone pareiasaurs all show skin armour. The features of this armour are described as found virtually complete in a small pareiasaur, identified here as an about half-grown Pareiasaurus serridens. Different in skin structure from this small pareiasaur is the dwarf-form, Nanoparia pricei. A few particulars have now been added to the known skin structure of this species. It is suggested that Cistecephalus zone pareiasaurs can be referred to 2 principal species: the one is Pareiasaurus serridens Owen, to which all the incomplete and variably grown specimens can be assigned such as the genus Propappus and some other species from the genera Pareiasaurus, Anthodon and Nanoparia. The other consists of the single specimen Nanoparia pricei. Further affinities are beyond existing evidence to settle.
Main article
Keywords: pareiasaur; Cistecephalus zone; South Africa